2013
DOI: 10.1016/j.pocean.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Canary current upwelling: More or less?

Abstract: International audienceIt has been hypothesized that coastal upwelling in the four major eastern boundary current systems might be intensified as global warming could result in a greater land-sea temperature gradient and hence strengthen alongshore winds. Recent research has suggested a substantial increase of upwelling intensity off Northwest Africa. Evidence there is based on the derivation of a proxy for upper ocean temperatures from the alkenone unsaturation index (View the MathML sourceU37K′) derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(96 citation statements)
references
References 55 publications
3
91
1
1
Order By: Relevance
“…While there have been a number of studies on this topic (Diffenbaugh et al, 2004;Di Lorenzo et al, 2005;Auad et al, 2006;Bakun et al, 2015), the Intergovernmental Panel on Climate Change 5th Assessment Report (IPCC AR5) has concluded that there is low confidence in projections regarding upwelling (Stocker et al, 2013;Barros et al, 2014). In part, this is a result of the substantial spatial heterogeneity in physical characteristics within EBUS, which emphasizes the role of local processes and resultant local biotic effects (Nelson and Hutchings, 1983;Dorman and Winant, 1995;Barton et al, 2013;Bakun et al, 2015). However, the low confidence in predictions regarding the ecological future of EBUS is driven more heavily by uncertainty surrounding the potentially counteracting effects of intensifying winds on the one hand, and increasing thermal stratification on the other.…”
Section: Benguelamentioning
confidence: 99%
See 3 more Smart Citations
“…While there have been a number of studies on this topic (Diffenbaugh et al, 2004;Di Lorenzo et al, 2005;Auad et al, 2006;Bakun et al, 2015), the Intergovernmental Panel on Climate Change 5th Assessment Report (IPCC AR5) has concluded that there is low confidence in projections regarding upwelling (Stocker et al, 2013;Barros et al, 2014). In part, this is a result of the substantial spatial heterogeneity in physical characteristics within EBUS, which emphasizes the role of local processes and resultant local biotic effects (Nelson and Hutchings, 1983;Dorman and Winant, 1995;Barton et al, 2013;Bakun et al, 2015). However, the low confidence in predictions regarding the ecological future of EBUS is driven more heavily by uncertainty surrounding the potentially counteracting effects of intensifying winds on the one hand, and increasing thermal stratification on the other.…”
Section: Benguelamentioning
confidence: 99%
“…Importantly, there is stronger agreement that significant trends of upwelling intensification are evident at higher latitude for all EBUS. Among studies excluded from the meta-analysis, either because they did not meet the strict selection criteria or because they were published after the analysis was completed, most (Di Lorenzo et al, 2005;Alves and Miranda, 2013;Barton et al, 2013;Bylhouwer et al, 2013;Stocker et al, 2013;Cropper et al, 2014;deCastro et al, 2014;Jacox et al, 2014;Sydeman et al, 2014b;Varela et al, 2015) show results consistent with the findings of Sydeman et al (2014a). Those containing seemingly contradictory results (Demarcq, 2009;Dewitte et al, 2012) add uncertainty, but do not refute the findings of the metaanalysis, as they focus on local regions, use short time series and do not add uncertainty.…”
Section: Trends In Upwelling-favorable Windsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wind observations and reanalysis products are controversial regarding the Bakun intensification hypothesis (Bakun, 1990). Using different wind databases for the Canary region, Barton et al (2013) concluded that there was no evidence for a general increase in the upwelling intensity off northwest Africa. Marcello et al (2011) found an intensification of the upwelling system in the same area during a 20-year period, while the alongshore wind stress remained almost stable.…”
Section: Introductionmentioning
confidence: 99%